Ukuran Perusahaan, Leverage, Sales Growth dan Agresivitas Pajak - Antari, Ni Kadek Dwi Putri; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p04, 2022)
Tax aggressiveness is a plan to reduce the tax burden through tax planning. The purpose of this study was to determine the effect of firm size, leverage, and sales growth on tax aggressiveness using the ETR proxy. This study uses LQ45 Index companies listed on the IDX for the 2016-2020 period. The method of determining the sample is non-probability sampling with purposive sampling technique and totaling 35 observations. The data collection method is non-participant observation and uses multiple linear regression analysis techniques. The results showed that company size had a negative effect on tax aggressiveness, while leverage and sales growth had a positive effect on tax aggressiveness. Keywords: Firm Size; Leverage; Sales Growth; Tax Aggressiveness.